A Review of the Effects of Physical Activity and Exercise on Cognitive and Brain Functions in Older Adults. (11th September 2013) - Bherer, Louis; Erickson, Kirk I.; Liu-Ambrose, Teresa
Abstract : Studies supporting the notion that physical activity and exercise can help alleviate the negative impact of age on the body and the mind abound. This literature review provides an overview of important findings in this fast growing research domain. Results from cross-sectional, longitudinal, and intervention studies with healthy older adults, frail patients, and persons suffering from mild cognitive impairment and dementia are reviewed and discussed. Together these finding suggest that physical exercise is a promising nonpharmaceutical intervention to prevent age-related cognitive decline and neurodegenerative diseases.